Optimizing DNA extraction methods for Nanopore sequencing of Neisseria gonorrhoeae direct from urine samples - Street, TL; Barker, L; Sanderson, ND; Kavanagh, J; Hoosdally, S; Cole, K; Newnham, R; Selvaratnam, M; Andersson, M; Llewelyn, MJ; O'Grady, J; Crook, DW; et al. (American Society for Microbiology, 2019)
Background. Empirical gonorrhoea treatment at initial diagnosis reduces onward transmission. However, increasing resistance to multiple antibiotics may necessitate waiting for culture-based diagnostics to select an effective treatment. There is a need for same-day culture-free diagnostics that identify infection and detect antimicrobial resistance. Methods. We investigated if Nanopore sequencing can detect sufficient N. gonorrhoeae DNA to reconstruct whole genomes directly from urine samples. We used N. gonorrhoeae spiked urine samples and samples from gonorrhoea infections to determine optimal DNA extraction methods that maximize the amount of N. gonorrhoeae DNA sequenced whilst minimizing contaminating host DNA. Results. In simulated infections the Qiagen UCP Pathogen Mini kit provided the highest ratio N. gonorrhoeae to human DNA and the most consistent results. Depletion of human DNA with saponin increased N. gonorrhoeae yields in simulated infections, but decreased yields in clinical samples. In ten urine samples from men with symptomatic urethral gonorrhoea, ≥92.8% coverage of an N. gonorrhoeae reference genome was achieved in all samples, with ≥93.8% coverage breath at ≥10-fold depth in 7 (70%) samples. In simulated infections if ≥104 CFU/ml of N. gonorrhoeae was present, sequencing of the large majority of the genome was frequently achieved. N. gonorrhoeae could also be detected from urine in cobas PCR Media tubes and from urethral swabs, and in the presence of simulated Chlamydia co-infection. Conclusion. Using Nanopore sequencing of urine samples from men with urethral gonorrhoea sufficient data can be obtained to reconstruct whole genomes in the majority of samples without the need for culture.